UAE-Belém work programme on indicators: Presentation on progress and recommendations target 9b (food & agriculture) expert group - Hussain, Abid; Tonui, Charles; Wolf, Julia; Astigarraga, Laura; Njuguna, Lucy; Rai, Neha; Dasgupta, Shouro; Wong, Theresa (2025)
The document presents work by the Target 9b (Food & Agriculture) Expert Group under the UAE–Belém Work Programme on Indicators (June 2025). It frames Target 9b (decision 2/CMA.5) as aiming for climate-resilient food and agricultural production, resilient supply and distribution systems, more sustainable/regenerative production, and equitable access to adequate food and nutrition by 2030. It describes an indicator-development process: breaking down the target into components, reviewing existing indicator sets, identifying gaps, proposing new indicators, then testing and refining them against agreed quality criteria.